7 - Commissions of Inquiry: The Hybrid Hollowing Out of State Governance in South Africa - Pooe, TK (Africa Development, 2026)
The release in mid-2022 of The Judicial Commission of Inquiry into Allegations of State Capture Report brought the number of completed official commissions of inquiry (CoIs) since 2001 to twelve. Currently, there has been a substantial increase in the use and establishment of CoIs. This article contends that the establishment of CoIs in inappropriate circumstances should be seen as a disturbing practice by the African National Congress (ANC)-led government to outsource its political and institutional leadership role to quasi-legal arrangements like CoIs. This article uses Rational Choice Theory/ Choice Theory to examine the terms of reference of two recent CoIs. It then contends that there has been a marked decline in state capacity, and that appointing CoIs due to ANC political party decisions is a form of the hybrid ‘hollowing out of state governance’, which involves outsourcing governance and leadership to CoIs. This jeopardises the government’s ability to address socio-economic and institutional public policy problems. New government usage standards are needed to guide decisions on when it is indeed appropriate in South Africa to establish a CoI to examine and report on an important societal concern.